Sensitive determination of carbidopa through the electrochemiluminescence of luminol at graphene‐modified electrodes. (13th August 2014) - Hosseini, Morteza; Mirzanasiri, Nooshin; Rezapour, Morteza; Sheikhha, Mohammad Hasan; Faridbod, Farnoush; Norouzi, Parviz; Ganjali, Mohammad Reza
Abstract Using the concept of electrogenerated chemiluminescence (ECL), a sensitive analytical method for the determination of carbidopa is described. Electro‐oxidation of carbidopa on the surface of a graphene oxide (GO)‐modified gold electrode (GE) leads to enhancement of the weak emission of oxidized luminol. Under optimum experimental conditions, the ECL signal increases linearly with increasing carbidopa concentrations over a range of 1.0 × 10‐9–1.7 × 10‐7 M, with a detection limit of 7.4 × 10‐10 M. The proposed ECL method was successfully used for the determination of carbidopa in urine samples. Copyright © 2014 John Wiley & Sons, Ltd.